Influence of nitrogen fertilizer dose on blast disease of finger millet caused by Pyricularia grisea - and RASHMI YADAV, BIJENDER KUMAR* (Indian Phytopathology, 2012)
The effects of four nitrogen fertilizer doses on the development of blast disease of finger millet were studied on six cultivars under field conditions at Gaja Research Station of GBPUAT, Hill Campus, Ranichauri, Tehri Garhwal, Uttarakhand, during 2006 and 2007. The six cultivars (PRM 9802, GPU 45, VR 708, GPU 28, RAU 8 and VL 149) included all reaction types (resistant, susceptible, moderately resistant/susceptible) to blast. Four levels of nitrogen (0, 20, 40 and 60 kg N/ha) applications were tested over two years at the same location. The results indicated that the neck and finger blast increased with increasing N levels. However, 40 kg N/ha was found optimum for maintaining low disease without sacrificing the yield. Furthermore, differential cultivar response to nitrogen was observed. While, maximum incidence of neck and finger blast was recorded in the cultivar RAU 8 at 60kgN/ha. GPU 45, GPU 28 and VL 149 showed complete resistance at all the levels of nitrogen.